Cost Efficiency for Effective Revenue Mobilisation at the Mmdas in Ghana - Dr. Jennifer Ellah Adaletey, Qais Ahmed Almaamari, Mr. Raymond Achiyaale (Mathematical Statistician and Engineering Applications, 2023)
This study assesses the cost efficiency of the MMDAs in their revenue mobilization by: identifying the revenue sources for Ho Municipal Assembly; examining the revenue mobilization strategies adopted by Ho Municipal Assembly, and examining the cost efficiency of the revenue mobilization strategies adopted by Ho Municipal Assembly. The study sampled data using convenience sampling method and a structured questionnaire as the data collection instrument.